Kepemilikan Institusional dan Kompensasi Bonus Serta Pengaruhnya terhadap Manajemen Laba pada Perusahaan Asuransi yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2019 - Novi Susyani; Santi Maria; Cucu Hodijah (Cakrawala Repositori IMWI, 2020)
This study aims to determine the effect of institutional ownership and bonus compensation both simultaneously and partially on earnings management in insurance sector issuers on the Indonesia Stock Exchange (BEI) 2017-2019. The type of research used is verification research or hypothesis testing research. By using the census method and unbalanced panel data, there were 68 observation companies that met the population criteria. The type of data used is secondary data obtained from the capital market reference center on the Indonesia Stock Exchange. Multiple regression analysis model is used to test the hypothesis. The results of this study indicate that (1) Institutional ownership has a negative effect on earnings management. (2) bonus compensation has a negative effect on earnings management, and (3) Institutional ownership and bonus compensation simultaneously have an effect on earnings management.